Physiological Responses While Carrying Load under Different Modes in Laboratory Conditions - Dhyani, Vijayshree; Sharma, P; Thakur, T C (Journal of Agricultural Engineering, 2009)
Changes in the physiological responses due to loads, modes, and grades were studied in laboratory. Seven hill women subjects in age group of 35±3 years were selected through non-probability sampling. Time spent (8 min), speed (3.0 km/h) and type of load (sand bag) was kept constant for each combination. A total of 27 different combination of treatments with total loads of 15, 20 and 25 kg carried on back, head and shoulders on zero, 5 % and 10 % grades were selected. The physiological data was collected from 5th till 8th minute for each combination. ANOVA showed significant differences with loads, modes and grades in heart rate and oxygen consumption rate. The highest mean value of HR (150 beat/min) and OCR (1.42 l/min) occurred for carrying 25 kg load on shoulder at 10% grade, and the lowest mean value HR(106 beat/min) and OCR(0.62 l/min) for carrying 15 kg load on back at zero-grade. Back mode of carrying load was physiologically least demanding than those of head and shoulder modes with all the loads and grades.